An Analysis of Reading Strategies used by male and female students - Syafarudin Ahmad (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Reading activity has the main purpose to find information by comprehending the message originated from a written source. As stated by Harmer (2008), reading is an active mental process intended to gain information and comprehend the message in the text. To read effectively, it is necessary for the reader to apply strategies that suit their reading needs. Another aspect that influences reading strategies is gender as gender differs personality of individuals that affects learning strategies (Anantasa, 2016). Therefore, the researcher is interested in conducting a study about the difference between reading comprehension strategies used by males and females. This study used a descriptive qualitative research method and semi-structured interviews as the instrument. The data for this research were collected from 10 students with 5 male and 5 female students of the English department from the University of Islam Malang online with the use of WhatsApp voice notes. The data are analyzed using qualitative analysis that consists of data reduction, grouping, coding, and interpretation to get the data as a whole. In result shows that most of the participants in this study are active readers. with female students tend to be more frequent and consistent while male students tend to be more focused in reading. The study indicated that the reasons for using strategies depend on the characteristic of the text, preference, and reading purposes. The study also indicated many differences in terms of using reading strategies, male students are dominant at previewing, skimming, and predicting, while female students are dominant at text Identification, summarizing, attention to detail, and selecting a strategy. The study suggests the importance of conducting a study on digital reading settings as reading is gradually shifted to the digital setting.Key Words: Reading strategies, gender, reading comprehension.